The Impact of Strategic Cost Management Methods on Supporting the Continuity of Food Manufacturing Companies: A study on a sample of food manufacturing companies in Khartoum State - Abdalla, Mohammed Ishag (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to know the impact of strategic cost management methods on supporting the continuity of the firm in the Sudanese food industrial sector through strategic cost management methods, namely target costing, value chain, and resource consumption accounting. The study adopted the descriptive analytic method. The survey form was used to collect field data from workers in the food industrial sector in Khartoum State through purpoive sampling method from the community of the study, which is one of the non-cermmonial samples that allows the researcher to obtain information from specific sources . The study used the stepwise analysis to test the hypotheses. The study found that there is a strong direct correlation between strategic cost management methods and firm continuity. The study recommended increasing the awareness of cost accountants in the Sudanese industrial sector of the importance of the information derived from strategic cost management methods as one of the basic pillars of the continuity of industrial firms.